Comparative Study on the Implementation of Accrual-Based Regional Government Accounting Standards at the Human Resources Development Agency of the Province of West Sumatra - ., Dessy; ., Heryanto (Archives of Business Research, 2018)
This study aims to compare the implementation of Accrual-Based Regional Government Accounting Standards carried out in the Human Resources Development Agency of West Sumatra Province with the forwarding of Government Accounting Standards according to Permendagri Number 64 of 2013 which refers to PP No. 71 of 2010. The method used in this study is Comparative descriptive research method with qualitative descriptive analysis approach. The data used is secondary data in the form of financial statements in 2015 to 2017 along with transaction evidence and supporting documents related to Accrual Based Accounting. While the primary data was collected through interview methods in order to strengthen the analysis of accrual-based accounting processes in the Human Resources Development Agency of West Sumatra Province. The results showed that the implementation of Accrual-based Regional Government Accounting Standards at the Human Resources Development Agency of West Sumatra Province as a whole was very in accordance with the Minister of Home Affairs Regulation No. 64 of 2013 and PP No. 71 of 2010 with an average level of suitability of 80.69%. Where the financial statements produced are very in accordance with the criteria of financial statements according to Permendagri Number 64 of 2014 with a level of suitability of 83.33%, the recognition process is in accordance with Accrual-Based Accounting Standards with a level of conformity of 75.00%, while the process of measurement and presentation Revenue, Expenditures, Expenses, Inventories and Fixed Assets are very much in accordance with Permendagri Number 64 of 2013 which refers to PP No. 71 of 2010 with a level of suitability of 83.75%.